High Glucose Accelerates Autophagy in Adult Rat Intervertebral Disc Cells - Kong, Chae-Gwan; Park, Jong-Beom; Kim, Man Soo; Park, Eun-Young (Asian spine journal, 2014)
In vitro cell culture. The purpose of this study was to investigate the effect of high glucose on autophagy in adult rat intervertebral disc cells. Diabetes mellitus is considered to be an important etiologic factor for intervertebral disc degeneration, resulting in degenerative disc diseases. A glucose-mediated increase of autophagy is a major causative factor for the development of diseases associated with diabetes mellitus. However, no information is available for the effect of high glucose on autophagy in adult intervertebral disc cells. Nucleus pulposus and annulus fibrosus cells were isolated from 24-week-old adult rats, cultured and placed in either 10% fetal bovine serum (normal control) or 10% fetal bovine serum plus two different high glucose concentrations (0.1 M and 0.2 M) (experimental conditions) for one and three days, respectively. The expressions of autophagy markers, such as beclin-1, light chain 3-I (LC3-I) and LC3-II, autophagy-related gene (Atg) 3, 5, 7 and 12, were identified and quantified. Two high glucoses significantly increased the expressions of beclin-1, LC3-II, Atg3, 5, 7, and 12 in adult rat nucleus pulposus and annulus fibrosus cells in a dose- and time-dependent manner. The ratio of LC3-II/LC3-I expression was also increased in a dose-respectively time-dependent manner. The results suggest that autophagy of adult nucleus pulposus and annulus fibrosus cells might be a potential mechanism for the intervertebral disc degeneration in adult patients with diabetes mellitus. Thus, the prevention of autophagy in adult intervertebral disc cells might be considered as a novel therapeutic target to prevent or to delay the intervertebral disc degeneration in adult patients with diabetes mellitus.